Dampak Upah Minimum Terhadap Pendapatan, Kesehatan Dan Pendidikan Pada Kabupaten/Kota Di Kalimantan Barat - Stella Melin; Lusia Sedati; Agusandi (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2026)
The minimum wage can affect the income, health, and education of people in West Kalimantan. This research approach used a quantitative method by distributing questionnaires via Google Form to 1,000 respondents who were employed and identified as working in West Kalimantan. The results showed that the minimum wage had no impact on income in West Kalimantan. While incomes increased, some businesses in the agriculture, plantation, and other sectors also increased. The government's minimum wage policy did not impact unemployment and poverty because people's incomes remained stable, and many people still received wages below the government-set standard. This also had no impact on education or public health. Keywords: Minimum Wage; Income; Health; Education; Welfare